Effect of different spray volumes on deposition characteristics of a fuel-operated UAV sprayer using herbicides in transplanted rice (Oryza sativa) - JEEVAN, NARAYANASWAMY; PAZHANIVELAN, SELLAPERUMAL; KUMARAPERUMAL, RAMALINGAM; RAGUNATH, KALIAPERUMAL; ARTHANARI, P MURALI; SRITHARAN, N; KARTHIKKUMAR, A; MANIKANDAN, S (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted at the Agricultural Research Station, Tamil Nadu Agricultural University, Bhavanisagar, during 2021–23 to study the effect of spray volume (SV) on deposition characteristics of a fuel-operated UAV sprayer (25 L/ha, 37.5 L/ha and 50 litre/ha) and knapsack sprayer (KS) (500 litre/ha) in the rice (Oryza sativa L.) field. Results showed that herbicides spraying using UAV (37.5 litre/ha) had a higher droplet deposition (0.077 and 0.075 μL/cm2) than knapsack spraying of 500 litre/ha (0.06 and 0.049 μL/cm2) in the ground layer of first (PE) and second (PoE) spraying, respectively. KS (500 litre/ha) had significantly higher droplet coverage rate, droplet size (Dv0.5) over other UAV spray volumes. Subsequently, variation in spray uniformity was found between two sprayers. Among UAV spray volumes, application of 50 litre/ha had better deposition, coverage rate and number of spray deposits/cm2 compared to UAV (37.5 litre/ha), with no significant difference between them. Further, application of 25 litre/ha using UAV recorded lower deposition characteristics over other treatments. So, considering low volume application of UAV (37.5 litre/ha), comparable with high volume KS (500 litre/ha), it is better to go for optimal application of UAV (37.5 litre/ha), which is having better working efficiency, profitability and labor-saving approach compared to knapsack sprayer.